POTENSI ARKEOLOGIS DAERAH ALIRAN SUNGAI KIKIM KABUPATEN LAHAT, SUMATERA SELATAN - Prasetyo, Sigit Eko (Jurnal Penelitian Arkeologi Papua dan Papua Barat, 2012)
Archaeology is the study of human society, primarily through the recovery and analysis of the material culture and environmental data that they have left behind. One of the archaeological data found in Kikim River, Lahat Regency South Sumatra and has been reported by the archaeologist years before. Although the report was very potential, not so many researches have led in Kikim River up until 2008. In 2008 Kikim River and its branches showed many stone tools on the surface. The research began around the River by surveying the surface and taking stone artifacts. These stone artifacts determined by stone tool characteristics and technology. From survey, 134 stone tools had been found in Kikim River, Saling River, Pangi River, and Mpayang River.